Uji Aktivitas Ekstrak Daun Miana Coleus Atropurpureus Sebagai Antibakteri Staphylococcus aureus dan Escherichia coli - Alif Rahman Habibi; Adi Arianto; Astrid Siska Pratiwi; Duta Bintang Ramadhan (CV. ALIM'SPUBLISHING, 2024)
The Miana Coleus atropurpereus plant is a unique plant because it has so many varieties. The differences in these varieties can be seen from the very diverse differences in leaf color. Several studies have known about the active antimicrobial compounds of Coleus atropurpereus miana leaves, namely in the form of flavonoids, saponins, steroids, tannins, essential oils, eugenol, polyphenolic compounds, alkaloids, ethyl salicylate, calcium oxalate, rosmarinic acid compounds. In this study, Escherichia coli and Staphylococcus aureus bacteria were used using thick extracts that had been macerated using 96% alcohol. in this study it showed 8 mm at a concentration of 50%, at a concentration of 25% it showed a clear zone of 7 mm and at a concentration of 12.5% ​​it showed 6 mm. It can be concluded that the extract of Coleus atropurpereus miana leaves is weakly toxic to E. coli and not toxic to S. aureus bacteria..